2015
DOI: 10.1074/jbc.a114.212856
|View full text |Cite
|
Sign up to set email alerts
|

Novel human homologues of p47 and p67 participate in activation of superoxide-producing NADPH oxidases.

Abstract: PAGE 25238:The image shown in the lower panel on the left of Fig. 3A was not correct. The lower panel on the left (the first from the left) incorrectly duplicated the lower panel on the right (the third from the left). In addition, the panels in Fig. 3A were not oriented correctly. The revised figure includes the correct images in the proper orientation. This correction does not affect the interpretation of the results or the conclusions of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 0 publications
1
34
0
3
Order By: Relevance
“…It is known that Nox1 constitutively produces superoxide in cells coexpressing Noxo1 and Noxa1, and cell stimulation with PMA, a potent activator of PKC, leads to a marked increase in superoxide production . To study the role of PKC in PMA‐induced enhancement of Nox1 activity, we tested the effect of GF109203X, an inhibitor of PKC , on the Nox1‐based oxidase reconstituted in CHO cells . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is known that Nox1 constitutively produces superoxide in cells coexpressing Noxo1 and Noxa1, and cell stimulation with PMA, a potent activator of PKC, leads to a marked increase in superoxide production . To study the role of PKC in PMA‐induced enhancement of Nox1 activity, we tested the effect of GF109203X, an inhibitor of PKC , on the Nox1‐based oxidase reconstituted in CHO cells . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been shown that Nox1‐catalyzed ROS production in vascular smooth muscle cells is enhanced upon stimulation with angiotensin II, platelet‐derived growth factor and enthothelin‐1 . Consistent with these observations, the Nox1‐based oxidase reconstituted in cultured cells can also be further increased in a manner dependent on cell stimulants such as PMA and angiotensin II . However, the mechanism for the stimulus‐induced enhancement of Nox1 activity is not well understood.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations